Hybrid modulation strategy for the Vienna rectifier - Molligoda, Devinda (2021)
The Vienna rectifier can produce three voltage levels, however only the connection to the neutral-point is fully controllable using the bidirectional switches. When the neutral-point voltage is not imposed in a phase-leg, the polarity of the pulses generated depends on the diode that is conducting in that phase-leg, which is defined by the current direction. As a result, the voltage pulses generated can go in the opposite direction to what is demanded by the controller, and the current becomes distorted. This can be mitigated by injecting a particular zero sequence so that the reference voltage is clamped to the neutral-point during the intervals where the current of a phase leg has the opposite sign than its reference voltage. However, the converter is at risk of entering into overmodulation when operating with high modulation indices. In this paper, a hybrid modulation strategy is introduced where a calculated minimal amount of reactive current depending on the operating conditions is injected to avoid overmodulation. The reduction of reactive current required compared to the state-of-the-art solutions is up to 100% in certain operating conditions. With the proposed method, the Vienna rectifier can operate in a wide range of power factors without compromising the quality of the source currents. The concept is verified by simulation and in a 1-kW Vienna rectifier experimental setup.